2000
DOI: 10.1143/jjap.39.5679
|View full text |Cite
|
Sign up to set email alerts
|

Electronic States of Perovskite-Type Oxides and Ferroelectricity

Abstract: A relation between B-site transition metal and ferroelectricity is investigated in A BO3 perovskite-type oxides. We focus on intensity of the covalent bonds between the B-site atom and the oxygen octahedron and evaluate Harrison's covalency parameter α. The density functional theory within the local density approximation is adopted to obtain the valence electron energy levels of free atoms from which the covalency α is calculated. Strong correlation between the covalency α and the Curie tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 11 publications
2
30
0
2
Order By: Relevance
“…As reported for BaTiO 3 and PbTiO 3 [76,77], the PDOS of the Ti-3d states are found in the valence band (VB, −5 to 0 eV) due to the dynamic charge transfer, i.e., the orbital hybridization between the 3d states of Ti and the 2p states of the neighboring O forming the short bonds with Ti. It is interesting to note that Bi has some PDOS of 6p in the VB resulting from the Bi-6p-O-2p hybridization, which is similar to the Pb-6p-O-2p one reported for PbTiO 3 [78]. In contrast, Na has almost no PDOS in the VB, showing that Na has an ionic nature in BNT.…”
Section: +supporting
confidence: 71%
“…As reported for BaTiO 3 and PbTiO 3 [76,77], the PDOS of the Ti-3d states are found in the valence band (VB, −5 to 0 eV) due to the dynamic charge transfer, i.e., the orbital hybridization between the 3d states of Ti and the 2p states of the neighboring O forming the short bonds with Ti. It is interesting to note that Bi has some PDOS of 6p in the VB resulting from the Bi-6p-O-2p hybridization, which is similar to the Pb-6p-O-2p one reported for PbTiO 3 [78]. In contrast, Na has almost no PDOS in the VB, showing that Na has an ionic nature in BNT.…”
Section: +supporting
confidence: 71%
“…According to Miyazawa et al, the hybridization between the O 2p and Pb 6p orbitals is the main reason for large oxygen displacements and high ferroelectricity in the PbTiO 3 compound. 16 The reduction of the O 2p -Ti 3d and O 2p -Pb 6p hybridizations in the PLT samples as the amount of lanthanum increases could therefore be related to the modification observed in the ferroelectric behavior of the PLT samples with increasing amounts of lanthanum.…”
Section: B O K-edge Xanes Resultsmentioning
confidence: 95%
“…[11][12][13]15 Theoretical calculations have shown that hybridized states of Ti 3d and O 2p and covalent bonding of Pb-O crucially affect ferroelectric stability in the PbTiO 3 compound. 16,17 Different features observed in the O K-edge spectra of mixed perovskite ferroelectric compounds have also been interpreted in terms of hybridization between O 2p and Ti 3d, and O 2p and Pb 6p orbitals. 12 On the other hand, the features observed at the Ti L 3,2 edges in different ABO 3 and in mixed perovskite compounds have been attributed to various factors, some of which are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…But as Ca2 concentration increases in the structure this hybridization weakens and in crystal ionic interaction starts and ionic-size effect is manifested [9,12]. At initial stages of calcium concentrations (upto 20-30 %) coulomb forces are expected to dominate.…”
Section: Resultsmentioning
confidence: 99%